2002
DOI: 10.1152/ajpregu.00560.2001
|View full text |Cite
|
Sign up to set email alerts
|

The use of microcomputed tomography to study microvasculature in small rodents

Abstract: The use of microcomputed tomography to study microvasculature in small rodents. Am J Physiol Regulatory Integrative Comp Physiol 282: R1267-R1279, 2002 10.1152/ajpregu.00560.2001.-Appropriate nephron function is dependent on the intrarenal arrangement of blood vessels. The preferred and primary means to study the architecture of intrarenal circulation has been by filling it with opaque substances such as india ink, radio-opaque contrast material, or various polymers for study by light or scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 81 publications
3
110
0
Order By: Relevance
“…The micro-computed tomography protocol is listed last (V), but should be considered to have comparable preparation complexity to protocol III. This protocol is optimized for ex vivo visualization of brain vasculature [Bentley et al, 2002].…”
Section: Imaging Protocolsmentioning
confidence: 99%
“…The micro-computed tomography protocol is listed last (V), but should be considered to have comparable preparation complexity to protocol III. This protocol is optimized for ex vivo visualization of brain vasculature [Bentley et al, 2002].…”
Section: Imaging Protocolsmentioning
confidence: 99%
“…A promising new technique, microcomputed tomography ( -CT) (Jorgensen et al, 1998), enables the study of the spatial arrangement of the vasa vasorum in large specimens (Lerman and Ritman, 1999;Bentley et al, 2002;Wan et al, 2002;Gössl et al, 2003), even in its frozen state (Kantor et al, 2002). In conjunction with semiautomated tree analysis software, it can provide quantitative geometrical data not yet available by other techniques (Gössl et al, 2003).…”
mentioning
confidence: 99%
“…Similarly, Schneider et al [81] studied the murine hind limb vasculature using corrosion casts with both mCT and SR CT. Razavi et al [82] imaged the pulmonary and cardiac circulation using mCT. A review of mCT imaging of vascular networks can be found in Bentley et al [83] and more recently in Zagorchev et al [84].…”
Section: Micro-computed Tomographymentioning
confidence: 99%